Methylation of SFRP2 gene as a promising noninvasive biomarker using feces in colorectal cancer diagnosis: a systematic meta-analysis - Yang, Qihua; Huang, Tao; Ye, Guoliang; Wang, Bojun; Zhang, Xinjun (Scientific reports, 2016)
Methylation of secreted frizzled-related protein genes (SFRP) associated with the Wnt signaling pathway has previously been reported. However, the diagnostic role of SFRP methylation in colorectal cancer (CRC) remains unclear. A systematic search was performed to identify eligible articles for analysis. The pooled OR showed that SFRP1 , SFRP2 , SFRP4 and SFRP5 methylation was significantly higher in CRC and benign mucosal lesions than in normal colonic mucosa. When CRC was compared to benign mucosal lesions, SFRP1 and SFRP2 methylation had a significantly higher OR, but methylated SFRP4 and SFRP5 had a similar OR. Moreover, the pooled sensitivity, specificity and AUC (area under the curve) of methylated SFRP2 in feces of patients with CRC vs. healthy subjects was 0.71, 0.94 and 0.94, respectively. Therefore, methylation of SFRP1 and SFRP2 may be significantly correlated with CRC. However, in a study with small sample size, methylated SFRP4 and SFRP5 were not shown to be closely associated with CRC. Additionally, detection of SFRP2 methylation in feces presents a potential noninvasive biomarker for CRC diagnosis.